The evolution of Indonesian SAI maturity: Oversight, insight, and foresight functions of health-themed performance audits - Andrianto, Nico; Basuki, J; Karunia, R. Luki; Nurdin, Nurliah (Badan Pemeriksa Keuangan Republik Indonesia, 2024)
The maturation of Supreme Audit Institutions varied considerably across countries, shaped by numerous factors influencing their development trajectory. This research examines the evolutionary maturation of the health sector performance audits conducted by Badan Pemeriksa Keuangan (BPK), distinguishing itself from previous studies focusing on capability development, implementation process, evaluation of government policy effectiveness, or assessment of BPK’s performance audits. Amid the limited research on Supreme Audit Institutions (SAI) maturity models across various countries, this study aims to address this gap in the existing literature. A mixed-methods approach was employed, analyzing 840 health-related performance audit reports and BPK viewpoints from 2008 to 2023. This analysis was complemented by a comprehensive literature review and triangulated through interviews with auditors and auditees. The findings reveal that BPK’s maturity development was influenced by multiple factors, encompassing the adoption of new public management concepts, efforts to achieve the National Medium-Term Development Plan (RPJMN), the impact of the COVID-19 pandemic, and the integration of Sustainable Development Goals (SDGs). It is recommended that in the future, BPK should prioritize the most recent public issues more. Furthermore, to enhance BPK’s maturity, it is essential to incorporate an insight- and foresight-driven approach with thematic performance audits.